Elevated soluble urokinase plasminogen activator receptor serum levels indicate poor survival following transarterial chemoembolization therapy for hepatic malignancies: An exploratory analysis. Issue 3 (1st February 2021) - Loosen, Sven H; Schulze‐Hagen, Max; Vucur, Mihael; Gorgulho, Joao; Paffenholz, Pia; Benz, Fabian; Mohr, Raphael; Demir, Münevver; Wree, Alexander; Kuhl, Christiane; Trautwein, Christian; Tacke, Frank; et al.
Abstract: Background and Aim: Transarterial chemoembolization (TACE) represents a standard of care for patients with intermediate‐stage hepatocellular carcinoma (HCC) or liver metastases. However, identification of the ideal candidates for TACE therapy remains challenging. The soluble urokinase plasminogen activator receptor (suPAR) has recently evolved as a prognostic marker in patients with cancer; however no data on suPAR in the context of TACE exists. Methods: Serum levels of suPAR were measured by an enzyme‐linked immunosorbent assay in n = 48 TACE patients (HCC: n = 38, liver metastases: n = 10) before intervention and 1 day after TACE, as well as in 20 healthy controls. Results: Serum levels of suPAR were significantly elevated in patients with liver cancer compared to healthy controls. Patients with or without an objective tumor response to TACE therapy had comparable levels of circulating suPAR. Importantly, baseline suPARs above the ideal prognostic cut‐off value (5.39 ng/mL) were a significant prognostic marker for reduced overall survival (OS) following TACE. As such, patients with initial suPAR levels >5.39 ng/mL showed a significantly reduced median OS of only 256 days compared to patients with suPAR serum levels below the cut‐off value (median OS: 611 days). In line with previous data, suPAR serum concentrations correlated with those of creatinine but were independent of tumor entity, leukocyte count, and C‐reactive protein in multivariate analysis. Conclusion: Baseline suPAR serum levels provide important information on the postinterventional outcome of liver cancer patients receiving TACE. Abstract : suPAR serum concentrations represent a previously unrecognized marker indicating prognosis in patients receiving TACE.